2006
DOI: 10.1242/jeb.02376
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide mediates hypoxia-induced relaxation of trout urinary bladder smooth muscle

Abstract: Inhibitors of H 2 S synthesis also inhibited hypoxic relaxation. These experiments suggest that H 2 S is a phylogenetically ancient gasotransmitter in nonmammalian non-vascular smooth muscle and that it serves as an oxygen sensor/transducer, mediating the effects of hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…Addition of exogenous cysteine, which presumably enhances or sustains H 2 S production, augments hypoxic relaxation of trout urinary bladder (31) and salmon intestine (32). Consistent with findings in other tissues, inhibitors of H 2 S biosynthesis inhibit hypoxic relaxation of rainbow trout urinary bladder (31) and rainbow trout and Coho salmon intestine (32).…”
Section: Other Tissuessupporting
confidence: 56%
See 1 more Smart Citation
“…Addition of exogenous cysteine, which presumably enhances or sustains H 2 S production, augments hypoxic relaxation of trout urinary bladder (31) and salmon intestine (32). Consistent with findings in other tissues, inhibitors of H 2 S biosynthesis inhibit hypoxic relaxation of rainbow trout urinary bladder (31) and rainbow trout and Coho salmon intestine (32).…”
Section: Other Tissuessupporting
confidence: 56%
“…Hypoxia and H 2 S also relax nonvascular smooth muscle of fish urinary bladder and the gastrointestinal tract, both of these stimuli produce a unique and transient increase in spontaneous contraction frequency and amplitude before the onset of the inhibitory effects (31,32). H 2 S also relaxes human corpus cavernosum and urinary bladder smooth muscle (24,45).…”
Section: Other Tissuesmentioning
confidence: 99%
“…[20][21][22] We observed in the midst of H 2 S, the relaxation of smooth muscle precontracted with acetylcholine chloride. Streng et al 20 investigated the transient receptor potential vanilloid receptor 1 and showed that it might be involved in the contraction induced by NaHS when rat bladder strips were electrically stimulated.…”
Section: Discussionmentioning
confidence: 80%
“…Patacchini et al 21 reported Expression and function of hydrogen sulphide in human and rat bladder JW Gai et al 694 that intravesical NaHS instillation increased protamine sulphate pretreated rat bladder pressure. Dombkowski et al 22 explored the H 2 S effects on trout bladder smooth muscle and suggested that H 2 S could produce a dose-dependent relaxation in unstimulated and carbachol pre-contracted bladders and inhibit spontaneous contractions. KCl, adrenergic and cholinergic agonists would usually be chosen to precontract smooth muscle in not only LUT but also cardiovascular vessels, gastrointestinal tract, and corpus cavernosum tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, assuming that H 2 S is the vasoactive sulfide moiety, anoxic turtles did not display hemodynamic responses to NaHS despite the fact they experienced a greater exogenous H 2 S exposure than normoxic turtles and the amount of H 2 S produced upon infusion of 30 mol/kg NaHS exceeded the estimated circulating plasma H 2 S levels. However, the local intracellular concentration of H 2 S produced endogenously by vascular smooth muscle (12,26,48,83,84) may have been higher. If the activation of the signaling pathway of H 2 S-mediated vasoconstriction is maximal during anoxia, it would be expected that R sys and/or P sys should fall, and/or G sys increase, in response to antagonists of endogenous H 2 S production.…”
Section: Does H 2 S Contribute To the Increased R Sys Of Anoxic Turtles?mentioning
confidence: 99%